ICT infused Print to Audio Textbooks: Studying the Effect on English and Hindi Reading Comprehension in Inclusive Classroom - Bharti (Indian Journal of Educational Technology, 2021)
The present research attempts to study the effect of JCT based aural reading with the use of handheld device called "Smart Speak" through specially printed textbooks on the English and Hindi reading comprehension of students studying in class 5. Smart Speak looks like a thick pen which converts printed text into speech. This helps students'facing challenges in reading print to meaningfully engage with the printed text. A batch of 31 sighted students and 3 students with Visual Impairments (VI) studying in class 5, in inclusive education settings, formed the sample for this study. After establishing the reading proficiency of participating students in English Braille, English Print, Hindi Braille and Hindi Print, researcher made Reading Comprehension Tests was administered as pre-test. The same reading comprehension test was used both as the pre-test and post-test. The purpose of pre-test was to establish non-familiarity of students with the text selected for the intervention. The use of the same test as post-test provided the measure of effect of intervention on the reading comprehension. The data analysis indicated that the JCT based aural reading intervention was found to be statistically extremely significant in enhancing the reading comprehension in both English and Hindi for students with and without VI studying in inclusive classroom.